“All texts are texts.” - Maria Larsson (Acta Didactica Norden)
Teachers’ text choice and the activities they assign their students when reading the texts impact what students learn. The design of the assignments also direct students’ attention toward what is implicated as important in the text, which is why how reading instruction is designed in the classroom is important to whether students’ reading development is successful. The aim of this study is to contribute knowledge about how non-fiction and fiction is used in the classroom in the L1-subject Swedish at upper-secondary school, and thus what students have the opportunity to learn in the classroom. The study draws on qualitative data from interviews with five teachers of Swedish in upper-secondary school and their teaching material for the course Swedish 1 during a school year.